Artificial Octopus-Limb-Like Adhesive Patches for Cupping-Driven Transdermal Delivery with Nanoscale Control of Stratum Corneum - Lee, Jihyun; Hwang, Gui Won; Lee, Bum Soo; Park, No-June; Kim, Su-Nam; Lim, Dohyun; Kim, Da Wan; Lee, Yeon Soo; Park, Hyoung-Ki; Kim, Seulgi; Kim, Jin Woong; Yi, Gi-Ra; et al. (American Chemical Society, 2024)
Drug delivery through complex skin is currently being studied using various innovative structural and material strategies due to the low delivery efficiency of the multilayered stratum corneum as a barrier function. Existing microneedle-based or electrical stimulation methods have made considerable advances, but they still have technical limitations to reduce skin discomfort and increase user convenience. This work introduces the design, operation mechanism, and performance of noninvasive transdermal patch with dual-layered suction chamber cluster (d-SCC) mimicking octopus-limb capable of wet adhesion with enhanced adhesion hysteresis and physical stimulation. The d-SCC facilitates cupping-driven drug delivery through the skin with only finger pressure. Our device enables nanoscale deformation control of stratum corneum of the engaged skin, allowing for efficient transport of diverse drugs through the stratum corneum without causing skin discomfort. Compared without the cupping effect of d-SCC, applying negative pressure to the porcine, human cadaver, and artificial skin for 30 min significantly improved the penetration depth of liquid-formulated subnanoscale medicines up to 44, 56, and 139%. After removing the cups, an additional acceleration in delivery to the skin was observed. The feasibility of d-SCC was demonstrated in an atopic dermatitis-induced model with thickened stratum corneum, contributing to the normalization of immune response.